2019
DOI: 10.1103/physreva.100.012514
|View full text |Cite
|
Sign up to set email alerts
|

Maxwell eigenmode approach to the Casimir-Lifshitz torque

Abstract: More than forty years ago, Barash published a calculation of the full retarded Casimir-Lifshitz torque for planar birefringent media with arbitrary degrees of anisotropy. An independent theoretical confirmation has been lacking since. We report a systematic and transparent derivation of the torque between two media with both electric and magnetic birefringence. Our approach, based on an eigenmode decomposition of Maxwell's equations, generalizes Barash's result for electrically birefringent materials, and can … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 42 publications
(75 reference statements)
0
5
0
Order By: Relevance
“…In the uniaxial limit, this theory yields the exact non-retarded result of Barash while for the retarded case, the results were found to match numerically for reasonable values of the perturbative parameter 4 . Very recently, Broer et al reported an independent derivation via Maxwell eigenmode approach confirming Barash's results 5 .…”
Section: Introductionmentioning
confidence: 53%
“…In the uniaxial limit, this theory yields the exact non-retarded result of Barash while for the retarded case, the results were found to match numerically for reasonable values of the perturbative parameter 4 . Very recently, Broer et al reported an independent derivation via Maxwell eigenmode approach confirming Barash's results 5 .…”
Section: Introductionmentioning
confidence: 53%
“…( 12) with Eq. ( 13) restores the known Fresnel reflection matrix [21,24] for a semi-infinite birefringent plate.…”
Section: B Lifshitz Formulamentioning
confidence: 94%
“…We start by formulating Maxwell's equations as an eigenvalue problem, as we have done before for the case of single interfaces [24]. Assume that the electromagnetic (EM) wave propagates within one of the anisotropic slabs labeled as j whose anisotropic plane is facing the surface, which is defined as the x-y-plane in the laboratory coordinate system.…”
Section: A Transfer Matrixmentioning
confidence: 99%
See 1 more Smart Citation
“…[51] that the Casimir repulsion can be enhanced by increasing the dielectric permittivity along the normal direction and/or reducing the dielectric permittivity along the transverse principal directions. For the configuration in which the optic axes are oriented perpendicular to the surface normal, two possibilities emerge: firstly, it becomes possible to tune the force between attraction and repulsion by changing the misalignment angle between the optic axes of the slabs; and secondly, a van der Waals torque also appears concurrently with the van der Waals force [57][58][59][60]. Such a torque arises, owing to a dielectric mismatch in the azimuthal direction, in the same way that a force arises due to a dielectric mismatch in the surface normal direction.…”
Section: Van Der Waals Torque Between Birefringent Topological Insulatorsmentioning
confidence: 99%